1997
DOI: 10.3186/jjphytopath.63.316
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fertile Magnaporthe grisea Fungus Pathogenic to Rice in Yunnan Province, China.

Abstract: Three hundred eight isolates of Magnaporthe grisea were collected from rice plants in 14 counties of Yunnan Province, China in 1988-89. Each isolate was tested for mating type and fertility with Matl-1 and Matt-2 female fertile tester strains. Three percent of these isolates consisted of Matt-1, and 23% of Matt-2. The remaining 74% isolates did not produce perithecia in crosses with both Matl-1 and Matl-2 fertile testers. The percentage of fertile isolates in each county ranged from 90% in Lincang to 0% in Lij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Moreover, hermaphroditic strains identified in some restricted areas lead to the assumption that sexual reproduction could occur in the field (Wang and Valent, 2009 ). Hermaphroditic isolates are rare and previous studies showed that hermaphroditic strains could be found in Thailand, India, Philippines, and Yunnan province of China (Hayashi et al, 1997 ; Kumar et al, 1999 ; Mekwatanakarn et al, 1999 ). In this study, hermaphroditic strains are found in four regions, three of them locate in the northeastern of the Sichuan Basin and isolates collected in five regions have both the mating types ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hermaphroditic strains identified in some restricted areas lead to the assumption that sexual reproduction could occur in the field (Wang and Valent, 2009 ). Hermaphroditic isolates are rare and previous studies showed that hermaphroditic strains could be found in Thailand, India, Philippines, and Yunnan province of China (Hayashi et al, 1997 ; Kumar et al, 1999 ; Mekwatanakarn et al, 1999 ). In this study, hermaphroditic strains are found in four regions, three of them locate in the northeastern of the Sichuan Basin and isolates collected in five regions have both the mating types ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the sample populations of M. grisea from rice in Argentina are similar to populations from rice in other countries with respect to mating-type distribution and fertility status [13,22,23,25,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Kyu89-246 is compatible (virulent) and Kyu77-07A is incompatible (avirulent) with Nipponbare. To produce the inoculum, 12-day-old M. grisea cultures growing on oatmeal agar (Hayashi et al 1997) at 26掳C were washed off by gentle rubbing with a water-soaked paintbrush and then placed under continuous illumination with near-UV light (360 nm, 18 W, Toshiba FL20S BLB; Toshiba Co., Tokyo) at 21掳C for 3-5 days to induce sporulation. Spores were harvested by washing the cultures with water, and the spore suspension was adjusted to 100,000 to 600,000 spores/ ml.…”
Section: Inoculation Of Rice With Rice Blastmentioning
confidence: 99%